Investigating the effects of gamma radiation on selected chemicals for use in biosignature detection instruments on the surface of Jupiter's moon Europa. (1st October 2019) - Freissinet, Caroline; Millan, Maëva; Glavin, Daniel P.; Li, Xiang; Grubisic, Andrej; Eigenbrode, Jennifer E.; Stern, Jennifer C.; Dworkin, Jason P.; Buch, Arnaud; Szopa, Cyril; Guzman, Melissa A.; Carts, Martin A.; et al.
Abstract: Jupiter's moon Europa is a prime target for the search for potential signs of life in the solar system. The Europa Lander Science Definition Team Report outlined investigations and measurement requirements on a future Europa Lander and has led us to consider application of powerful techniques such as pyrolysis and derivatization gas chromatography mass spectrometry (GC-MS) and laser desorption mass spectrometry (LD-MS) to elucidate the organic composition of near-surface ice and minerals. Definitive identification of chemical biosignatures using such techniques is strongly enabled by the use of various chemicals, such as perfluorotributylamine (PFTBA) for the MS calibration, α-cyano-hydroxycinnamic acid (CHCA) for matrix-assisted laser desorption and ionization (MALDI) and N, N-dimethylformamide dimethyl acetal (DMF-DMA), N- tert -butyldimethylsilyl-N-methyltrifluoroacetamide (MTBSTFA) and tetramethylammonium hydroxide (TMAH) for wet chemistry GC-MS protocols. The jovian radiation environment is known to represent a uniquely challenging risk to mission performance and lifetime, principally due to high radiation levels. To assess the potential ionizing radiation damage to these important chemicals, we tested their effectiveness following gamma radiation exposure doses up to the anticipated Europa Lander rating requirement of 300 krad(Si). The chemicals were sealed in glass ampules under vacuum (<10 mTorr), to reduce trapped oxygen gas, as the oxidation by O2 may be enhanced in the presence of radiation. We report that all five chemicals exposed to total ionizing doses of 0, 150 and 300 krad(Si) maintained their full effectiveness, and no significant degradation was observed. Highlights: Europa Lander payload radiation was simulated with 150–300 krad of gamma radiation. Resistance of five experimental reagents to radiation was investigated. No significant changes in the chemicals' structure or function were observed. LD-MS and GC-MS are relevant to seek biosignatures in a high radiative environment.